Multimodal robotic system for upper-limb rehabilitation in physical environment - Jorge A Díez; José M Catalán; Luis D Lledó; Francisco J Badesa; Nicolás Garcia-Aracil (Advances in Mechanical Engineering, 2016)
This article researches the feasibility of use of a multimodal robotic system for upper-limb neurorehabilitation therapies in physical environments, interacting with real objects. This system consists of an end-effector upper-limb rehabilitation robot, a hand exoskeleton, a gaze tracking system, an object tracking system, and electromyographic measuring units. For this purpose, the system architecture is stated, explaining the detailed functions of each subsystem as well as the interaction among them. Finally, an experimental scenario is designed to test the system with healthy subjects in order to check whether the system is suitable for future experiments with patients.